Cancer and malnutrition were independently associated with a poor prognosis in patients with heart failure. Issue 1 (January 2022) - Miyanaga, Satoru; Komukai, Kimiaki; Kubota, Takeyuki; Shirasaki, Keisuke; Oki, Yoshitsugu; Yoshida, Ritsu; Fukushima, Keisuke; Maehara, Tomoki; Yamamoto, Hiromasa; Niijima, Akira; Yoshimura, Michihiro
Highlights: Heart failure patients with cancer showed disturbed nutrition. Long-term mortality in heart failure patients with cancer was high. Malnutrition was associated with mortality, independently of cancer. Multidisciplinary treatment is needed for treating heart failure patients with cancer. Cancer therapies should be considered to avoid adverse effects on the heart. Abstract: Background: Recent advances in treatment have improved the survival of cancer patients. Such survivors may go on to develop heart failure (HF) later in life. HF and cancer are wasting diseases, and malnutrition is associated with a poor prognosis in patients with HF or cancer. Methods and Results: Patients admitted to our hospital with HF from April 2012 to March 2020 were retrospectively reviewed. They were divided into 2 groups: cancer patients ( N = 185) and patients without cancer ( N = 930). Patients discharged alive and followed by our outpatient clinic were also examined ( N = 857, median follow-up period: 794 days). Results: In cancer patients, the geriatric nutritional risk index and prognostic nutritional index were lower and the controlling nutritional status score was higher than in HF patients without cancer; nutrition was disturbed in HF patients with cancer. The in-hospital mortality rates of the two groups were not markedly different; however, cancer patients showed higher long-term mortality in comparison to HF patients without cancer. A multivariate analysis revealed that cancer and malnutrition were independently associated with all-cause death. Conclusions: The long-term mortality of HF patients with cancer was higher than that of HF patients without cancer. Malnutrition was associated with long-term mortality, independently of the presence of cancer. Multidisciplinary treatment is needed when treating HF patients with cancer. Graphical abstract: Image, graphical abstract